The Use of Accounting Information by Financial Analysts in Emergent Markets: The Case of Romania - Mihaela Ionascu; Ion Ionascu (Journal of Accounting and Management Information Systems (JAMIS), 2012)
The purpose of this paper is to investigate the use of accounting information by Romanian financial analysts with a focus on the models used and the factors affecting their forecasts accuracy. We hypothesize that on the emergent market of Romania, analysts rely more on simple valuation models (such as price multiples) and that accounting variables are perceived as less important compared to macroeconomic factors when it comes to forecast accuracy. To collect data we sent out questionnaires to the Research Departments of the brokerage companies authorized to operate on the Bucharest Stock Exchange (BSE) (investment firms, financial investments banks, credit institutions). As IFRSs became mandatory for consolidated accounts of listed companies and as the National Securities and Exchange Committee (CNVM) envisions the application of IFRS in the individual accounts of these companies, the paper also tries to capture the perception of Romanian financial analysts on the role plaid by IFRS adoption in reducing forecasts errors.
Keywords: M41; G29; 650; valuation models; accounting information; financial analysts; forecast accuracy; IFRS adoption in Romania